Discourse Formulation of the Supreme Leader's Statements on Changes in the Sexual Culture of Iranian Society - Edris Ramooz; Seyyed Hosein Sharafodin (Religion & Communication)
Discursive formulation of leadership statements about of dynamics of sexuality in Iranian society. Today, the study of sexual culture is one of the fundamental studies in the social sciences. The importance of this issue is that sexual instinct can be considered as the driver and starting point of the process of meaning-making in human society. Therefore, semantics, interaction and reproduction of sexuality in relation to other dimensions and structures of the social system (culture, religion, economy, politics, law, education, media, etc.) on the one hand can lead to social order. And on the other hand lead to social turmoil and anxiety. This has led to different approaches and discourses around it; Discourses that analyze changes in sexual culture in their layers and axes of discourse and suggest strategies appropriate to their discourse in interacting and dealing with its changes. In the present article, an attempt has been made to formulate a discourse using the operational method of discourse analysis , the statements of the Supreme Leader as a social thinker about the changes in the sexual culture of Iranian society. Because each discourse analyzes the changes in sexual culture in terms of the impact of certain factors, goals and strategies. In this study, four discourse axes related to semantic components, central signifiers and causes and factors of sexual culture changes in Iranian society have been discovered and formulated, which has been studied based on the theory of social change.